Analysis of The Influence of Production Costs, Promotion and Sales Volume on Net Profit at PT. XYZ - Ratilla Amanda Edwar (Greenation Research & Yayasan Global Resarch National, 2024)
This study aims to analyze the effect of production expenses, promotional expenses, and sales volume on Net Profit at PT XYZ. Production expenses include all costs associated with manufacturing products, while promotional expenses include costs incurred to introduce products to consumers. Sales volume, as a measure of revenue, plays a crucial role in determining the company's Net Profit. The research method used is a literature review with a descriptive qualitative approach, collecting data from various academic sources. The results showed that production expenses and promotional expenses have a positive influence on Net Profit, with sales volume as a significant variable in increasing Net Profit. This study concludes that optimizing production cost management and effective promotion strategies can increase company profitability.